High-function ternary intergrowth mineral superfine filler, preparation method and application thereof

CN122978749APending Publication Date: 2026-10-27青阳广源新材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611159206.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-01
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]本发明的目的在于针对现有无机填料人工复配结构松散、功能单一、性能不稳定,单一矿物填料综合性能差,传统研磨工艺易破坏矿物原生晶体的缺陷,提供一种高功能三元共生矿物超细填料及其制备方法和应用,依托原矿独有三相嵌生结构,搭配常温湿法梯度研磨工艺,完整保留矿物先天多功能特性,实现一剂多用,适配多类高分子制品

Benefits of technology

1)天然共生结构独特,不可人工复刻:本发明的原料为碳酸镁、白云石、滑石天然三相嵌生一体矿,晶粒晶间结合紧密,结构均匀稳定,与人工掺混的松散粉体存在本质区别。经XRD检测证实原料纯度高、晶体完整,产品批次稳定性极强,具备天然资源与技术双重壁垒。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978749A_ABST
    Figure CN122978749A_ABST
Patent Text Reader

Abstract

The application provides a high-function ternary intergrowth mineral superfine filler and a preparation method and application thereof, and belongs to the technical field of inorganic functional fillers.The preparation method comprises the following steps: mechanically crushing and screening a ternary intergrowth raw ore to obtain high-purity raw ore powder; and sequentially performing two-stage wet ball milling and secondary classification on the high-purity raw ore powder to obtain the high-function ternary intergrowth mineral superfine filler; and the ternary intergrowth raw ore is a magnesium carbonate-dolomite-talc ternary intergrowth raw ore.The raw material of the application is a natural three-phase intergrowth integrated ore of magnesium carbonate, dolomite and talc, the crystal grains are tightly combined, and the structure is uniform and stable; the normal-temperature wet gradient grinding process completely avoids the damage of high temperature and strong mechanical impact on the crystal, and the powder is free of crystal amorphization; the multifunctional raw ore is synergistic, and the comprehensive performance is comprehensively leading; the industrialization adaptability is strong, and the cost reduction effect is remarkable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of inorganic functional filler technology, and in particular to a high-functionality ternary symbiotic mineral ultrafine filler, its preparation method, and its application. Background Technology

[0002] Currently, inorganic fillers for polymer materials are mainly divided into two categories: artificially compounded powders and single natural mineral powders. Artificially compounded fillers are made by physically mixing multiple powders such as talc, dolomite, and calcium carbonate. The components are loosely bound, and phase separation and functional degradation are prone to occur during use. The performance of each component can also interfere with each other, resulting in poor synergistic effect. At the same time, the compounding process is complex and the production cost is relatively high.

[0003] Conventional single-mineral fillers often use raw materials such as dolomite, calcite, and marble, which have relatively limited functions, only providing basic filling and unable to simultaneously achieve multiple properties such as reinforcement, toughening, flame retardancy, and lubrication. Furthermore, traditional mineral powders are mostly processed using dry high-temperature grinding processes, and the high temperatures generated by high-speed friction can easily damage the original crystal structure of the minerals, further reducing the performance of the product.

[0004] Furthermore, current mainstream ultrafine fillers generally suffer from defects such as high oil absorption value, significant decrease in the mechanical properties of products under high-filling conditions, and insufficient hiding power, making it difficult to meet the stringent requirements of high-end home appliances, automotive plastics, high-end shoe materials, and films for fillers with multifunctionality, high stability, and high filling capacity. Most mainstream inorganic fillers on the market use single calcium carbonate, dolomite, or talc powders, or artificially and physically compound these powders in proportions. For example, conventional PVC fillers often use calcite ultrafine powder, which only has a basic filling function; artificially compounded ternary mineral powders are limited by mixing processes, resulting in loose bonding at the three-phase interface and weak synergistic function. At the same time, existing mineral powders are generally processed using dry high-speed grinding processes, which easily cause crystal damage and performance degradation. There are currently no reports on technologies that utilize naturally occurring three-phase intergrowth symbiotic minerals and employ a room-temperature, structure-preserving wet process to prepare multifunctional ultrafine fillers. Summary of the Invention

[0005] The purpose of this invention is to address the shortcomings of existing inorganic fillers, such as loose structure, single function, unstable performance, poor comprehensive performance of single mineral fillers, and easy damage to the original mineral crystals by traditional grinding processes. This invention provides a high-performance ternary symbiotic mineral ultrafine filler, its preparation method, and its application. Relying on the unique three-phase intergrowth structure of the original ore, and combined with a room-temperature wet gradient grinding process, it fully preserves the inherent multifunctional characteristics of the mineral, realizes multiple uses of one agent, and is suitable for various types of polymer products.

[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing high-performance ternary symbiotic mineral ultrafine fillers, comprising the following steps: 1) Mechanically crush and screen the ternary symbiotic raw ore to obtain high-purity primary ore powder; 2) High-purity virgin mineral powder is sequentially subjected to two-stage wet ball milling and secondary classification to obtain high-performance ternary symbiotic mineral ultrafine filler; The ternary symbiotic ore is a magnesium carbonate-dolomite-talc ternary symbiotic ore.

[0007] Preferably, the two-stage wet ball milling in step 2) is carried out at room temperature. The ball milling media for the two-stage wet ball milling is zirconia beads. The two-stage wet ball milling includes a first-stage coarse milling and a second-stage fine milling. The particle size of the zirconia beads used in the first-stage coarse milling is 18~22mm, and the particle size of the zirconia beads used in the second-stage fine milling is 5~7mm.

[0008] Preferably, the liquid medium in the two-stage wet ball milling is water.

[0009] Preferably, the rotation speed of the two-stage wet ball mill is 1500~3500 r / min, and the rotation speed of the wet ball mill is linked and matched with the classification frequency of the secondary classification.

[0010] As a preferred option, the particle size D50 of the high-performance ternary symbiotic mineral ultrafine filler is 2~5μm.

[0011] As a preferred option, the high-performance ternary symbiotic mineral ultrafine filler is divided into three specifications according to particle size: D50≤4.5μm, D50≤3.0μm and D50≤2.5μm.

[0012] The present invention also provides a high-performance ternary symbiotic mineral ultrafine filler prepared by the preparation method described above.

[0013] This invention also provides the application of the aforementioned high-functionality ternary symbiotic mineral ultrafine filler in polymer products.

[0014] The beneficial effects of this invention are: 1) Unique natural symbiotic structure, impossible to replicate artificially: The raw material of this invention is a natural three-phase intergrowth mineral of magnesium carbonate, dolomite, and talc, with tight intergranular bonding and a uniform and stable structure, which is fundamentally different from artificially mixed loose powders. XRD testing confirms that the raw material has high purity and intact crystals, and the product batches have extremely strong stability, possessing both natural resource and technological barriers.

[0015] 2) Exclusive process protects crystals and ensures zero functional degradation: The room temperature wet gradient grinding process completely avoids the damage to crystals caused by high temperature and strong mechanical impact, and the powder does not exhibit crystal amorphization; no grinding aids are added throughout the process, the original interfacial activity of the minerals is fully preserved, and it has excellent compatibility with the polymer matrix. There are no problems such as additive precipitation, odor, or aging during the processing, and the production process is green and environmentally friendly.

[0016] 3) Multifunctional native synergy, leading overall performance: In terms of mechanics, the rigid carbonate skeleton provides reinforcement, the three-phase interlaced structure provides toughening, and the mechanical properties of the product decay slowly under high filling conditions; in terms of processing, the native talc phase gives the powder self-lubricating properties, with moderate oil absorption, and is suitable for various processing technologies such as extrusion, calendering, and open milling; in terms of optics, the powder has high whiteness, and the multi-level crystal interface enhances light scattering and has excellent hiding power; in terms of safety, magnesium-based carbonate has natural flame retardant and smoke-suppressing capabilities, which can meet the requirements of fire-resistant products such as wires and cables and foam materials.

[0017] 4) Strong industrial adaptability and significant cost reduction effect: The process parameters are simple and controllable, and multi-specification series products can be mass-produced, covering multiple fields such as plastics, rubber, and foaming materials; The filler of this invention supports high proportion filling, which can significantly reduce the raw material cost of polymer products, has a wide range of market applications, and has extremely high industrialization value. Attached Figure Description

[0018] Figure 1 The X-ray diffraction pattern of the ultrafine multifunctional composite powder HS-718 prepared in Example 2. Detailed Implementation

[0019] This invention provides a method for preparing high-performance ternary symbiotic mineral ultrafine fillers, comprising the following steps: 1) Mechanically crush and screen the ternary symbiotic raw ore to obtain high-purity primary ore powder; 2) High-purity virgin mineral powder is sequentially subjected to two-stage wet ball milling and secondary classification to obtain high-performance ternary symbiotic mineral ultrafine filler; The ternary symbiotic ore is a magnesium carbonate-dolomite-talc ternary symbiotic ore.

[0020] In this invention, the ternary symbiotic ore is a natural ternary symbiotic ore, serving as the sole functional base material. The ore exhibits a geologically primary three-phase intergrowth structure. XRD analysis reveals that the phases consist solely of high-purity crystalline phases of magnesium carbonate, dolomite, and talc, with no impurity diffraction peaks or amorphous defects, demonstrating high crystal integrity. The ore exhibits uniform composition and stable mineral phase structure. The magnesium carbonate-dolomite-talc ternary symbiotic ore used in this invention is a rare mineral resource, representing a special intergrowth ore body formed over a long period under specific geological conditions.

[0021] The raw material used in this invention is a geologically formed three-phase intergrowth symbiotic mineral of magnesium carbonate, dolomite, and talc. These three types of grains are not simply physically stacked, but rather interpenetrate and interlock at the micrometer scale, forming a dense, cross-linked overall crystal network. Dolomite and magnesium carbonate constitute the mineral matrix framework, exhibiting high hardness and rigidity. Flaky talc grains are uniformly embedded in the interstices and surfaces of the carbonate crystals, forming a composite crystal morphology of "rigid matrix + flaky lubricating phase." The three-phase grains rely on geological mineralization to form intergranular forces, resulting in a bonding strength far exceeding the van der Waals forces of artificially blended powders, leading to extremely high overall structural stability. In artificially blended powders, various particles are independent and prone to separation under stress, exhibiting independent or even antagonistic functions. In contrast, the natural symbiotic mineral used in this invention contains all three phases within its ultrafine particles, allowing each filling unit to achieve multifunctional integration and maximize functional synergy.

[0022] The magnesium content in the ternary symbiotic ore is constant at 57746.892 ppm, mainly found within the crystal lattices of magnesium carbonate and dolomite. The high lattice bond energy of magnesium carbonates endows the crystals with excellent rigidity. Under heated conditions, magnesium carbonates undergo thermal decomposition, releasing inert gases, which is the material basis for the mineral's natural flame-retardant and smoke-suppressing properties. Simultaneously, the active magnesium sites on the mineral surface can form weak interfacial bonds with the molecular chains of polymer matrices such as PVC, PP, and rubber, effectively improving the compatibility of fillers and resins.

[0023] In this invention, the mechanical crushing and screening in step 1) removes the surface weathered layer, mud and other impurities, while retaining complete original crystalline particles to obtain high-purity original mineral powder.

[0024] In this invention, the two-stage wet ball milling in step 2) is preferably carried out at room temperature. The ball milling medium for the two-stage wet ball milling is preferably zirconia beads. The two-stage wet ball milling includes a first-stage coarse grinding and a second-stage fine grinding. The particle size of the zirconia beads used in the first-stage coarse grinding is preferably 18~22mm, more preferably 19~21mm, and more preferably 20mm. The particle size of the zirconia beads used in the second-stage fine grinding is preferably 5~7mm, more preferably 5.5~6.5mm, and more preferably 6mm.

[0025] In this invention, the time for the first-stage coarse grinding is preferably 15-20 min, more preferably 17-18 min; the time for the second-stage fine grinding is preferably 30-45 min, more preferably 35-40 min.

[0026] In this invention, the liquid medium in the two-stage wet ball mill is preferably water.

[0027] In this invention, only water is used as the liquid medium during the two-stage wet ball milling process, without adding any grinding aids. Water is added dropwise through the ball mill inlet, with the amount added to maintain normal wet grinding conditions. A two-stage zirconium bead gradient segmented room-temperature wet grinding process is employed, with liquid-phase thermal conductivity grinding at room temperature throughout the process. There is no high-speed frictional heat accumulation, and no high-temperature thermal damage occurs. The grinding process only physically refines the mineral particles, completely preserving the original ore's three-phase intergrowth crystal framework and primary grain bonding interface, without generating amorphous deteriorating phases.

[0028] In this invention, the rotational speed of the two-stage wet ball mill is preferably 1500~3500 r / min, more preferably 2000~3000 r / min, and even more preferably 2200~2500 r / min. The rotational speed of the wet ball mill is linked and matched with the classification frequency of the secondary classification.

[0029] In this invention, the particle size D50 of the high-functionality ternary symbiotic mineral ultrafine filler is preferably 2~5μm, and the high-functionality ternary symbiotic mineral ultrafine filler is further preferably divided into three specifications according to particle size: D50≤4.5μm, D50≤3.0μm and D50≤2.5μm.

[0030] The present invention also provides a high-performance ternary symbiotic mineral ultrafine filler prepared by the preparation method described above.

[0031] The high-performance ternary symbiotic mineral ultrafine filler of the present invention retains the original three-phase intergrowth structure of magnesium carbonate, dolomite and talc, and has multiple synergistic functions such as reinforcement, toughening, flame retardancy, lubrication and high coverage.

[0032] This invention also provides the application of the aforementioned high-functionality ternary symbiotic mineral ultrafine filler in polymer products.

[0033] In this invention, the polymeric products are preferably plastics, rubber, or foamed materials, and more preferably ethylene-vinyl acetate copolymer (EVA) foamed shoe materials, polyvinyl chloride (PVC) edge banding strips, PVC calendered films, modified polypropylene (PP) materials, wear-resistant rubber, wires and cables, plastic profiles, and plastic pipes.

[0034] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0035] In the embodiments, the ternary symbiotic ore is a magnesium carbonate-dolomite-talc three-phase integrated intergrowth symbiotic ore.

[0036] Example 1

[0037] The ternary symbiotic ore was mechanically crushed, washed, and screened to obtain high-purity primary ore. This high-purity primary ore was then fed into a ball mill for two-stage wet ball milling at room temperature. The milling chamber was compartmentalized, and the milling media was zirconia beads. In the first stage of coarse grinding, the zirconia beads had a particle size of 20 mm, a ball-to-material ratio of 3:1, and a grinding time of 18 min. In the second stage of fine grinding, the zirconia beads had a particle size of 6 mm, a ball-to-material ratio of 2.5:1, and a grinding time of 40 min. Water was added as a liquid medium during the two-stage wet ball milling process, dripped through the mill inlet, with the amount added maintained to maintain normal wet grinding conditions. The ball mill speed was 1800 r / min, synchronized with the secondary classification frequency of 35 Hz at a speed of 3000 r / min.

[0038] A secondary classification system with D50≤4.5μm was set up, and the ultrafine multifunctional composite powder HS-618 was obtained by matching it with the speed of wet ball milling.

[0039] The ultrafine multifunctional composite powder HS-618 in this embodiment is suitable for products such as PVC edge banding strips, color masterbatches, and modified PP.

[0040] Example 2

[0041] The ball mill was rotated at 2200 r / min. A secondary classification system was set up according to D50≤3.0μm. Other process conditions were the same as in Example 1, and ultrafine multifunctional composite powder HS-718 was obtained.

[0042] The ultrafine multifunctional composite powder HS-718 in this embodiment is suitable for general plastic products, EVA foam shoe materials, wear-resistant rubber and other products.

[0043] Example 3

[0044] The ball mill was rotated at 2500 r / min, and a secondary classification system was set up according to D50≤2.5μm. Other process conditions were the same as in Example 1, and ultrafine multifunctional composite powder HS-818 was obtained.

[0045] The ultrafine multifunctional composite powder HS-818 in this embodiment is suitable for products such as profiles, pipes, wires and cables, and PVC calendered films.

[0046] Comparative Example 1

[0047] Ultrafine calcium carbonate was prepared using dolomite as the raw ore and following the same process as in Example 2.

[0048] Comparative Example 2

[0049] Ultrafine calcium carbonate was prepared using calcite as the raw ore and following the same process as in Example 2.

[0050] Comparative Example 3

[0051] Ultrafine calcium carbonate was prepared using marble scraps (from Fayaling Mine, Yongfeng County, Jiangxi Province) as the raw ore, following the same process as in Example 2.

[0052] Figure 1 The X-ray diffraction (XRD) pattern of the ultrafine multifunctional composite powder HS-718 prepared in Example 2 is shown. The XRD was performed using a D8 ADVANCE X-ray diffractometer (Brook) according to JY / T 0587-2020 "General Rules for Polycrystalline X-ray Diffraction Methods". Figure 1 As can be seen, the spectrum only shows characteristic diffraction peaks for the three high-purity crystalline phases: magnesium carbonate, dolomite, and talc. There are no diffraction peaks for impurity minerals such as calcite, quartz, and clay. The spectrum baseline is flat, and no diffuse broad peaks corresponding to amorphous minerals are observed. The diffraction peaks of each phase are sharp, with narrow half-peak widths and peak positions that perfectly match the standard cards, proving that the original ore's three-phase intergrowth crystal structure is intact. The room-temperature wet grinding process did not cause lattice distortion, crystal breakage, or amorphization, and the original mineral phase structure was completely preserved. Traditional dry grinding easily produces crystal fracture and amorphization problems, resulting in baseline elevation and diffuse broad peaks in the XRD spectrum. The composite powder spectrum of this invention does not have these defects, fully demonstrating the structure-preserving advantage of this invention.

[0053] X-ray diffraction (XRD) verification shows that the method of this invention only achieves physical particle size refinement without damaging the mineral lattice and three-phase intergrowth interface, and the crystal integrity remains consistent with the original ore. Powders of different fineness retain the complete three-phase crystal structure and high magnesium composition characteristics of the original ore, while also possessing differentiated functional advantages, corresponding to different industrial product scenarios, forming a series of functional filler products.

[0054] The performance of the powders prepared in Examples 1-3 and Comparative Examples 1-3 was tested, and the results are shown in Table 1.

[0055] D50: Measured using a laser particle size analyzer, representing the particle size value corresponding to a cumulative distribution of 50%.

[0056] Oil absorption value: Tested according to the specifications in GB / T 19281-2014.

[0057] Whiteness: Tested according to GB / T 23774-2009.

[0058] Table 1. Performance of the powders in the examples and comparative examples

[0059] As can be seen from the data in Table 1, the ternary symbiotic mineral ultrafine filler of this invention exhibits a pattern where finer particle size leads to higher whiteness and a simultaneous increase in oil absorption, consistent with the characteristics of ultrafine mineral powders. Under the same particle size conditions, the oil absorption of the composite powder of this invention is close to that of traditional calcium carbonate fillers, without affecting the processing flowability of the substrate; its whiteness is far superior to that of dolomite and marble fillers, resulting in better appearance quality. Comparative Examples 1-3 are all single-phase mineral fillers, which can only achieve basic filling and lack multi-functional synergistic effects, exhibiting significant shortcomings in overall performance.

[0060] The composite powder prepared in Example 2 and the powders in Comparative Examples 1-3 were used as fillers and applied to PVC, respectively, and their performance was analyzed and compared.

[0061] The formulation of the filler for PVC is as follows (all parts are by weight): 100 parts of PVC (SG-5) (Cangzhou Julong Chemical Co., Ltd.), 18 parts of dioctyl terephthalate (DOTP) (Zhonghang New Materials (Shandong) Co., Ltd.), 4 parts of liquid barium cadmium zinc composite stabilizer (Wenzhou Zhengbang Chemical Co., Ltd.), and 60-70 parts of filler (60, 62, 64, 66, 68, and 70 parts were added in Example 2, and 60 parts were added in Comparative Examples 1-3).

[0062] According to the formula, accurately weigh each raw material, mix thoroughly, and then perform the mixing on a two-roll mill at a temperature of 170°C. After homogenization, stretch the mixture into films with a thickness of 0.3 mm and test the relevant properties. The entire two-roll mill and film stretching process should be completed within 10 minutes. Based on the addition of 60 parts of comparative examples 1-3, the addition amounts of the multifunctional ultrafine filler prepared in Example 2 were 60 parts, 62 parts, 64 parts, 66 parts, 68 parts, and 70 parts, respectively.

[0063] Tensile properties: Tested using a Chengde Jinjian UTM-1422 electronic universal testing machine in accordance with GB / T 528-2009.

[0064] Impact resistance: Tested according to GB / T 1843-2008 using Chengde Jinjian XJUD-5.5 electronic cantilever beam impact testing machine.

[0065] Opacity: Tested according to GB / T 23981.1-2019 "Determination of Opacity of Paints and Varnishes Part 1: Determination of Contrast Ratio of White and Light-colored Paints", using a CS-826 benchtop spectrophotometer from Hangzhou Caipu Technology Co., Ltd. Opacity is quantified by the contrast ratio, which is the ratio of the reflectance or reflectance density of the material on a black substrate to that on a white substrate. Contrast ratio = Y-value of the film on a black substrate (Y_black) / Y-value of the film on a white substrate (Y_white). The closer the contrast ratio is to 100%, the stronger the opacity. The smaller the difference in Y-values ​​of the same film on black and white substrates, the stronger the film's ability to block the substrate color (better opacity).

[0066] The test results are shown in Table 2.

[0067] Table 2 Performance test results of application in PVC

[0068] As can be seen from the performance comparison in Table 2: (1) Tensile strength: Under the same addition amount (60 parts), the tensile strength of Example 2 is 16.55 MPa, which is significantly higher than that of Comparative Examples 1 to 3. When the addition amount is in the range of 60 to 66 parts, the tensile strength continues to rise and reaches a peak of 17.01 MPa. After the filling amount continues to increase, the strength drops slightly. When the addition amount is 70 parts, it is still better than the benchmark value of traditional fillers, and the reinforcement effect is outstanding.

[0069] (2) Impact strength: With an addition amount of 60 parts, the impact strength of Example 2 is 11.66 kJ / m², and the toughening effect is obvious. As the amount of filler added increases, the impact strength decreases slowly. With an addition amount of 70 parts, it is still on par with the benchmark level of traditional fillers. The toughness decay is small under high filling.

[0070] (3) Covering power: The covering power of Example 2 increases continuously with the increase of the amount added. The values ​​of all gradients are far greater than those of traditional fillers, which can effectively reduce the amount of covering pigments such as titanium dioxide and reduce production costs.

[0071] The ternary symbiotic raw ore of the present invention relies on the inherent characteristics of different crystal phases to form five primary functions, each function working together: (1) Reinforcing mechanism: Magnesium carbonate and dolomite are granular rigid crystals with high crystal modulus and strong compressive strength. When the filler is uniformly dispersed in the polymer resin matrix, the rigid grains can serve as physical support points, share the external load on the product, restrict the slippage of the polymer molecular chain, and effectively improve the tensile strength of the material. (2) Toughening mechanism: When the material is impacted and microcracks are generated, the interlocked three-phase crystal network can deflect and blunt the crack tip, hindering the rapid propagation of the crack; at the same time, the lamellar talc has a certain slippage ability and can absorb impact energy. The rigid phase and the lamellar phase work together to allow the filler to achieve both rigidity enhancement and toughness improvement. (3) Lubrication and dispersion mechanism: Talc belongs to layered silicate crystals with weak interlayer bonding force and excellent self-lubricating properties. Since talc is embedded in the mineral particles and on the surface, it can greatly reduce the frictional resistance between powder particles, eliminating the need for additional grinding aids and processing lubricants. At the same time, it improves the dispersibility of the powder in the resin system and avoids particle agglomeration. (4) Flame retardant and smoke suppression mechanism: When polymer products are heated by fire, magnesium carbonate will undergo thermal decomposition: the decomposition process will absorb a large amount of heat, reducing the surface temperature of the substrate; at the same time, it will release carbon dioxide inert gas, diluting the concentration of oxygen and combustible smoke, isolating oxygen to inhibit the spread of combustion; the magnesium oxide generated by decomposition is a high-temperature resistant inorganic coating that covers the surface of the product, further blocking heat transfer and suppressing smoke overflow, achieving the dual effects of flame retardant and smoke suppression. (5) High hiding power mechanism: The overall whiteness of the mineral is excellent, and the granular carbonate and flaky talc form a multi-level scattering structure, so that light is reflected and scattered multiple times at different crystal phase interfaces, significantly improving the hiding power of the substrate color.

[0072] This invention adopts a room temperature two-stage gradient wet ball milling process, which is a special processing technology for ternary symbiotic minerals. Its core function is to preserve the original crystal structure and inherent function: (1) The whole process is room temperature wet processing, which relies on liquid water for heat conduction, completely eliminating the instantaneous high temperature generated by high-speed friction in traditional dry grinding, and avoiding thermal degradation problems such as thermal collapse of talc layered structure and premature decomposition of magnesium carbonate. (2) Gradient grinding with large and small zircon beads is used to adapt to the different Mohs hardness of magnesium carbonate, dolomite and talc. First, large zircon beads are used to complete coarse crushing, and then small zircon beads are used for precise refinement, ensuring that the three crystals are refined synchronously and uniformly, and there will be no situation of excessive crushing of a single component or crystal breakage. (3) Only water is used as the medium and no organic grinding aids are added, which fully preserves the original interfacial activity of the mineral, ensuring the binding ability of filler and polymer resin, and eliminating application defects such as precipitation, migration and aging of additives. (4) Combined with the secondary precision classification process, and the linkage matching of grinding speed and classification frequency, the particle size of powder can be precisely controlled to form multi-specification products to suit different application scenarios.

[0073] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a high-performance ternary symbiotic mineral ultrafine filler, characterized in that, It includes the following steps: 1) Mechanically crush and screen the ternary symbiotic raw ore to obtain high-purity primary ore powder; 2) High-purity virgin mineral powder is sequentially subjected to two-stage wet ball milling and secondary classification to obtain high-performance ternary symbiotic mineral ultrafine filler; The ternary symbiotic ore is a magnesium carbonate-dolomite-talc ternary symbiotic ore.

2. The preparation method according to claim 1, characterized in that, Step 2) The two-stage wet ball milling is carried out at room temperature. The ball milling media for the two-stage wet ball milling is zirconia beads. The two-stage wet ball milling includes a first-stage coarse grinding and a second-stage fine grinding. The particle size of the zirconia beads used in the first-stage coarse grinding is 18~22mm, and the particle size of the zirconia beads used in the second-stage fine grinding is 5~7mm.

3. The preparation method according to claim 1 or 2, characterized in that, The liquid medium in the two-stage wet ball milling is water.

4. The preparation method according to claim 3, characterized in that, The rotation speed of the two-stage wet ball mill is 1500~3500 r / min, and the rotation speed of the wet ball mill is linked and matched with the classification frequency of the secondary classification.

5. The preparation method according to claim 4, characterized in that, The particle size D50 of the high-performance ternary symbiotic mineral ultrafine filler is 2~5μm.

6. The preparation method according to claim 5, characterized in that, High-performance ternary symbiotic mineral ultrafine fillers are available in three specifications based on particle size: D50≤4.5μm, D50≤3.0μm, and D50≤2.5μm.

7. The high-functionality ternary symbiotic mineral ultrafine filler prepared by the preparation method according to any one of claims 1 to 6.

8. The application of the high-functionality ternary symbiotic mineral ultrafine filler as described in claim 7 in polymer products.